The relationship between logical- mathematical thinking and the ability to solve mathematical issue (A Field study with the eighth grade primary students in Lattakia City ) - Nassour, Raada (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
. This study aimed to identify the relationship between the logical mathematical thinking and the ability to solve mathematical issue to the eighth –grade primary students and to achieve this goal , the researcher applying the test logical mathematical thinking and test the ability to solve mathematical issue prepared by the researcher reaching study sample (150) students from the eighth grade in the main city of Lattakia . The results showed a strong correlation direct relationship between the scores of students (male female) to test the logical mathematical thinking and their scores on the ability to solve mathematical issue where this relationship suggest that the greater the degree of the students in the test of logical thinking increased their scores in the ability to solve Test Sports matter . And because the mathematical proof is a tool for thinking logical sense and flour among students is based on a holistic yiew and a careful analysis of the elements of the issue and then re-installed flexibly . The study suggested the need to develop educational programs that contribute to the development of mathematical reasoning among students , which may help in developing their skills in mathematical proof , and training teachers in the development of logical thinking , and provide the necessary training courses before and during service.